2009
DOI: 10.1016/j.mvr.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD146 is generated by ectodomain shedding of membrane CD146 in a calcium-induced, matrix metalloprotease-dependent process

Abstract: CD146 is a cell adhesion molecule localized at the endothelial junction and is involved in the control of cell cell cohesion. In this study, we showed that calcium influx in human microvascular lung endothelial cells results in the loss of surface CD146 and the release of soluble CD146. This calcium induced CD146 shedding could be prevented with inhibitors of matrix metalloproteases indicating a central role of matrix metalloproteases in this process. We also investigated if CD146 shedding influences vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
4
36
0
3
Order By: Relevance
“…CD146+ CD11b Ϫ cells were responsible for the vast majority of TG uptake in the lung. CD146 is a validated marker of pulmonary microvascular endothelial cells (38)(39)(40)(41). Therefore, our data strongly suggest that pulmonary microvascular endothelial cells participate in postprandial TG clearance.…”
Section: Role Of the Lungs In Tg Clearance During Cihsupporting
confidence: 53%
See 1 more Smart Citation
“…CD146+ CD11b Ϫ cells were responsible for the vast majority of TG uptake in the lung. CD146 is a validated marker of pulmonary microvascular endothelial cells (38)(39)(40)(41). Therefore, our data strongly suggest that pulmonary microvascular endothelial cells participate in postprandial TG clearance.…”
Section: Role Of the Lungs In Tg Clearance During Cihsupporting
confidence: 53%
“…3 and 4 ), we attempted to identify the cellular populations involved. We used CD11b as a macrophage marker ( 36,37 ) and CD146 as an endothelial cell marker (38)(39)(40)(41) in single-cell suspension of the lungs from mice…”
Section: Effect Of Cih On Tg Uptake By Different Cellular Populationsmentioning
confidence: 99%
“…In physiological conditions, MUC18 is considered as an intercellular adhesion molecule of cells like endothelial cells (3). Studies in human malignant melanoma strongly suggest that MUC18 is critical to tumor progression, such as metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether MUC18 should be included in the mucin (i.e., cell membrane-tethered mucins) family because it lacks the typical tandem repeat structure of mucins. Human MUC18 is a type I transmembrane glycoprotein with 646 amino acids (molecular weight, 113 kD) (2,3). MUC18 aberrant overexpression was initially identified in human malignant melanoma cells, which may promote tumor metastasis (4)(5)(6).…”
mentioning
confidence: 99%
“…28 We also observed that in vitro CD146 expression was dependent on oxygen levels and that in situ CD146 expression near the bone surface was absent or very weak. These observations might partly be explained by lower oxygen levels at the endosteum; however, additional mechanisms such as calcium-induced CD146 shedding might be operative as well, 33 because calcium levels are high near activated osteoclasts at the endosteal surface. 34 In summary, we have defined the phenotype of human primary nonhematopoietic BM-MSCs based on the expression of CD271, CD45, and CD146.…”
Section: Cd146 Expression and Bm-cfu-f In Situ Localization 5075mentioning
confidence: 99%